Bahasa Inggris - Ilmiyana, Abdiyati; Ellianawati; Widiarti, Nuni; Widiyatmoko, Arif (Universitas Veteran Bangun Nusantara, 2026)
Mathematics learning in elementary schools continues to face challenges related to low conceptual understanding, numeracy literacy, and student learning independence. In response to the demands of 21st-century education and the Merdeka Curriculum, student-centered and technology-based learning models are required. One such approach is Flipped Learning, which shifts content delivery outside the classroom and uses in-class time for active learning activities. This study aims to systematically review research trends and findings related to the implementation of Flipped Learning in elementary school mathematics learning during the 2019–2025 period. A Systematic Literature Review (SLR) was conducted on 12 national and international peer-reviewed articles identified through Google Scholar using the Publish or Perish application and analyzed thematically and bibliometrically with VOSviewer. The results indicate that Flipped Learning has a positive impact on students’ learning outcomes, conceptual understanding, numeracy literacy, motivation, and learning independence. However, its effectiveness is influenced by teacher readiness, quality of digital learning media, technological infrastructure, and parental support. Overall, Flipped Learning shows strong potential to support innovative mathematics learning aligned with 21st-century skills and elementary education curriculum goals